Evaluate the following

G

Guest

Guest
I just want someone to check my answer if that is okay.

x= -4

x(x-3)+2(x+1)
-4(-4-3)+2(-4+1)
16-12+-8+2
4+-8+2
-4+2
-2

Is this correct?
 

Daniel_Feldman

Full Member
Joined
Sep 30, 2005
Messages
252
Remember order of operations!

-4(-4-3)+2(-4+1)
16-12+-8+2 Not quite right here...See below
4+-8+2
-4+2
-2



-4(-4-3), so parentheses first.

-4(-4-3)=-4(-7)=28

I'll let you do the rest.
 
G

Guest

Guest
Good point! How about this?

x= -4

x(x-3)+2(x+1)
-4(-4-3)+2(-4+1)
-4(-7)+2(-3)
28+ -6
x=22
 

Daniel_Feldman

Full Member
Joined
Sep 30, 2005
Messages
252
Looks good!
 
Top